2001
DOI: 10.1128/jcm.39.1.222-227.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Mycobacterium bovis Isolates from Cameroon

Abstract: In order to gain a better understanding of the molecular epidemiology of Mycobacterium bovis isolates in Cameroon, 75 isolates of M. bovis collected in three provinces of northern Cameroon were studied by spoligotyping. For 65 of these isolates, typing was also carried out by pulsed-field gel electrophoresis (PFGE) with DraI, and 18 of the isolates were also typed by restriction fragment length polymorphism (RFLP) analysis with probe IS6110-RHS. Molecular typing of the isolates by these techniques revealed a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
39
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 13 publications
12
39
2
Order By: Relevance
“…It was shown that M. bovis was isolated from 5% of human isolates in Ibadan (Cadmus et al, 2006). Furthermore, spoligotype profiles of some M. bovis strains isolated in Nigeria had been previously reported by earlier studies in Cameroon (Njanpop-Lafourcade et al, 2001). In Mali, a strain with a similar spoligopattern to SB0944, reported previously in Nigeria, Chad and Cameroon was also observed in 13 of the 20 strains studied (Muller et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…It was shown that M. bovis was isolated from 5% of human isolates in Ibadan (Cadmus et al, 2006). Furthermore, spoligotype profiles of some M. bovis strains isolated in Nigeria had been previously reported by earlier studies in Cameroon (Njanpop-Lafourcade et al, 2001). In Mali, a strain with a similar spoligopattern to SB0944, reported previously in Nigeria, Chad and Cameroon was also observed in 13 of the 20 strains studied (Muller et al, 2008).…”
Section: Introductionsupporting
confidence: 74%
“…The four M. bovis spoligotype patterns were compared with the M. bovis spoligotype database (www.mbovis .org) to determine whether they had been previously described. Two patterns (SB0944 and SB0952) had been previously described by Njanpop-Lafourcade and colleagues (14) in a survey of M. bovis isolates from Cameroon, a country neighboring Nigeria. The remaining two patterns did not appear in the database and were therefore designated N4 and N5.…”
Section: Vol 44 2006 Analysis Of Nigerian M Tuberculosis Complex Smentioning
confidence: 74%
“…This is illustrated by two elements. First, the total number of spoligotypes is very high, relative to the total number of typed isolates, when compared to many other locations, especially islands like Great Britain (10) or Australia (12) and developing countries like Cameroon (31) or Tanzania (27). Second, the frequency of the two main spoligotypes (BCG-like and GB54) is low compared to studies in other countries.…”
Section: Vol 39 2001 Spoligotype Diversity Of French M Bovis Isolamentioning
confidence: 99%
“…As the BCG-like profile is the most conserved within the M. bovis subspecies in terms of the number of spacers, the hypothesis of an ancestral status of this profile is also corroborated by the accepted concept that the evolution of the DR region occurs by spacer deletions (15). It has also been sug-gested in the case of Cameroon that a BCG-like strain has constituted the parental strain for the M. bovis strains presently isolated in Cameroon, due to the similarity of the dominant spoligotype in this country with BCG-like (31).…”
Section: Vol 39 2001 Spoligotype Diversity Of French M Bovis Isolamentioning
confidence: 99%
See 1 more Smart Citation